Pengembangan Manajemen Pengayaan Literasi Berbasis Elektronik “LENTERA” Untuk Meningkatkan Kualitas Mengajar Guru di SMP Sentani - Andreas Resdianto; Listyani; Sophia Tri Satyawati (CV. Creative Tugu Pena, 2025)
This study aims to develop a digital literacy management system based on the LENTERA application to support literacy enrichment activities for junior high school students. The research employed a Research and Development (R&D) method, conducted through stages of needs analysis, design, development, expert validation, and product trials. The study was carried out in three schools in the Sentani area with diverse student characteristics and facility conditions. Research instruments included expert validation sheets, practicality questionnaires, and effectiveness analysis using statistical tests. The results indicate that the LENTERA application is feasible for use based on media and content expert validation, categorized as appropriate with minor revisions. In terms of practicality, teachers were able to operate the application easily without requiring complex technical training. The effectiveness test results show that the application usage scores were significantly higher than the reference value, indicating that the application effectively enhances students’ literacy enrichment activities. The LENTERA application implements a mastery learning system through sequential stages, including letters, sounds, syllables, words, and sentences, ensuring that students’ learning progress is based on material mastery. The main advantage of the product lies in the integration of educational management, gradual literacy learning, and interactive multisensory learning technology through a monitoring dashboard feature. Therefore, the LENTERA application can serve as a feasible, practical, and effective model for digital literacy management to support literacy learning in schools.